2017
DOI: 10.1002/cbf.3307
|View full text |Cite
|
Sign up to set email alerts
|

ATF1 and RAS in exosomes are potential clinical diagnostic markers for cervical cancer

Abstract: Cervical cancer is one of the most common cancers among women worldwide. It is highly lethal yet can be treated when found in early stage. Thus, early detection is of significant important for early diagnosis of cervical cancer. Exosomes have been used as biomarkers in clinical diagnosis. It is unknown that whether blood exosomes associated with cervical cancer can be detected and if these exosomes can accurately represent the developmental stage of cervical cancer. Mouse models were made out of a relapsed cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…For example, in cervical cancer models, activating transcription factor 1 (ATF1) and RAS genes were detected in the systemically circulating blood exosomes of the corresponding murine models. Interestingly, this study revealed that ATF1 and RAS genes were found significantly elevated in tumors of primary and recurrent cervical cancer in the mouse model, and they were also detected in the blood exosomes making them excellent biomarkers for cancer monitoring [54]. In the quest for alternative pancreatic cancer diagnostics, mutations in K-Ras and p53 were detected in the exosomal DNA obtained from serum of pancreatic cancer patients as well as established cell lines [55].…”
Section: Oncogenic K-ras In Exosomes and Cancer Diagnosticsmentioning
confidence: 99%
“…For example, in cervical cancer models, activating transcription factor 1 (ATF1) and RAS genes were detected in the systemically circulating blood exosomes of the corresponding murine models. Interestingly, this study revealed that ATF1 and RAS genes were found significantly elevated in tumors of primary and recurrent cervical cancer in the mouse model, and they were also detected in the blood exosomes making them excellent biomarkers for cancer monitoring [54]. In the quest for alternative pancreatic cancer diagnostics, mutations in K-Ras and p53 were detected in the exosomal DNA obtained from serum of pancreatic cancer patients as well as established cell lines [55].…”
Section: Oncogenic K-ras In Exosomes and Cancer Diagnosticsmentioning
confidence: 99%
“…Wnt/β-catenin, p38/MAPK, p53, and hedgehog signaling pathways were also reported to be related to carcinogenesis and progression in CC [13][14][15][16][17]. In addition, emerging molecules such as circular RNAs (circRNAs), long noncoding RNAs (lncRNAs), and exosomes were also shown to be related to the tumorigenesis of CC [18][19][20]. In recent decades, molecule-targetted therapy of CC has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…With the high mortality rate of cervical cancers, more information is needed regarding detection and treatment of the diseased. In this regard, several investigators have begun to examine extracellular vesicles (EVs) and their role in disease protection [2], as disease biomarkers [3][4][5] and/or as a cargo/vaccine agents for cervical cancer [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%